To study heterosis and genetic variability in Okra [Abelmoschus esculentus (L.) Moench]. - Sumit Kumar Mali; Neha Thomas; Abhinav Dayal (Annals of Agricultural Research, 2025)
A field experiment was conducted to study heterosis and genetic variability for yield and yield attributing traits, identify best crosses for growth and yield traits in Okra. Experimental material included 39 F1 hybrids developed by crossing 10 diverse parents. In kharif 2023 evaluation of 39 hybrids along with their 10 parents and 1 check variety Roma was sown in the RBD design with the distance of 45× 30 cm (R×R) (P×P) respectively in 3 replications. The findings revealed wide range of variability among all of the characters. Phenotypic coefficient of variation was higher than their corresponding genotypic coefficient of variation due to environmental effects ranged lowest for days to 50% flowering and higher values are for fruit weight indicated that environmental factor affect the most. Total of 19 characters out of 22 shows high heritability including plant height, fruit yield per plant etc. Maximum and positive significant heterosis was (26.52%) over mid parent exhibited by cross Punjab Padmani*CO-4 shows high yielding variety but negative heterosis for overall fruit yield in several crosses, and this impact might be due to the lack of synergistic effects between the parent lines.